Evaluation of a football fitness implementation initiative for an older adult population in a small-scale island society - Skoradal, May-Britt; Sjúrðarson, Tórur; Olsen, Helgi Winther; Leifsson, Eli Nolsøe; Pelikan, Vincent; Mohr, Magni; Davidsen, Annika Helgadóttir (Frontiers in Public Health, 2024)
Background The proportion of older people increases globally, which calls for sustainable interventions promoting healthy aging. Therefore, we aimed to evaluate the potential of Football Fitness as a sustainable model to promote quality of life, mental health, and physical function for older adult. Methods The study was conducted in collaboration with a municipality, a football club, and a university, and was designed as a randomized controlled trial. A total of 66 people (34 women, 32 men) older than 60 years were randomly assigned (60/40) to a Football Fitness (FOT) (n = 38, 20 women, 18 men) and a control group (CON) (n = 28, 14 women, 14 men). FOT participated in Football Fitness for 12 weeks. Quality of life (QoL) and mental wellbeing were determined pre-and post-intervention. Physical loading and Flow experience were measured in one representative training session. Blood pressure (BP), Yo–Yo Intermittent endurance test level 1 (Yo–Yo IE1), sprint performance, postural balance, and body composition were also performed pre-and post-intervention. Results An improvement in mental wellbeing was observed for both groups from pre- to post-intervention (p values <0.001) with no between-group differences. Regarding QoL, the environment domain improved in FOT compared to CON (p = 0.02). Mean Flow (M = 5.69; SD = 1.07) and perceived importance (M = 4.20; SD = 1.42) and average experienced difficulty was M = 5.23 (SD = 2.67), perceived skill (M = 5.23; SD = 2.56), and perceived balance (M = 5.64; SD = 1.56). These levels of flow can be characterized as being high. A between-group effect (p = 0.02) existed for systolic BP, which decreased (p < 0.01) by −5% [−8; −1%] in CON and remained unchanged in FOT. Both groups improved the Yo–Yo IE1 to a similar extent, with 28% [11; 44%] (p = 0.001) in FOT and 27% [9; 46%] in CON (p = 0.005). Postural balance improved (p = 0.004) by 38% [13; 63%] in FOT only, resulting in a superior (p = 0.01) balance score in FOT compared to CON post-intervention (p = 0.004). Conclusion Football Fitness improved the environmental quality of life domain and postural balance in older adults. Additionally, it appears to be a feasible group activity for older adults that promotes high flow and physical loading during training.